2020
DOI: 10.6004/jnccn.2019.7382
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Advanced Gastrointestinal Cancer in Relationship to Opioid Use: Findings From Eight Clinical Trials

Abstract: Background: This study assessed the patterns of opioid use among patients with advanced gastrointestinal cancers who were included in 8 clinical trials and evaluated the impact of opioid use on survival outcomes of included patients. Methods: Deidentified datasets from 8 clinical trials evaluating first-line systemic treatment of advanced gastrointestinal cancers were accessed from the Project Data Sphere platform (ClinicalTrial.gov identifiers: NCT01124786, NCT00844649, NCT00290966, NCT00678535, NCT00699374, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Notably, as the authors discuss, their findings contradict previous data from other retrospective analyses, which found opioid use correlated with worse survival in patients with advanced gastrointestinal cancer and specifically PDAC. 14,15 Thus, future work will need to confirm the findings from the current study with prospective designs, potentially including randomized trials of earlier symptom management for patients with PDAC. Additionally, interpreting retrospective cohort studies requires particular care to avoid several biases, including selection bias.…”
mentioning
confidence: 76%
“…Notably, as the authors discuss, their findings contradict previous data from other retrospective analyses, which found opioid use correlated with worse survival in patients with advanced gastrointestinal cancer and specifically PDAC. 14,15 Thus, future work will need to confirm the findings from the current study with prospective designs, potentially including randomized trials of earlier symptom management for patients with PDAC. Additionally, interpreting retrospective cohort studies requires particular care to avoid several biases, including selection bias.…”
mentioning
confidence: 76%
“…5 However, the inclusion of clinical trial participants may have led to inadvertent confounding by their use of novel therapies. 5 Another study found worse survival in 90 male patients with pancreatic cancer who received opioids, although this analysis focused on gonadal status, which may affect survival. 13 Studies by Steele et al and Oh et al assessing survival among patients who received opioids found that patients who required higher opioid doses had shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should continue to investigate the role of opioids and the effect of measures to mitigate pain and symptom management on pancreatic cancer survival. Brookdale Department of Geriatrics and Palliative Medicine, Icahn School of Medicine at Mount Sinai, New York, NY3 Geriatric Research, Education and Clinical Center, James J. Peters VA Medical Center, Bronx, NY4 Division of Digestive and Liver Disease, Department of Medicine, Columbia University Medical Center, New York, NY5 Division of Gastroenterology, Icahn School of Medicine at Mount Sinai, New York, NY6 Division of Gastroenterology, University of Miami Leonard Miller School of Medicine, Miami, FL CORRESPONDING AUTHOR Aimee L. Lucas, MD, MS, Division of Gastroenterology, Icahn School of Medicine at Mount Sinai, One Gustave L. Levy Place, Box 1069, New York, NY 10029; e-mail: aimee.lucas@mssm.edu.DISCLAIMERThe views expressed in this article are those of the authors and do not necessarily reflect the positions or policies of the Department of Veterans Affairs or the United States Government.…”
mentioning
confidence: 99%
“…Steele et al reported that high opioid use was associated with decreased survival (adjusted HR = 2.76; 95% CI: 1.39–5.48) in newly diagnosed stage IV PC [ 66 ]. Abdel-Rahman et al also reported that opioid use was associated with worse overall survival (HR, 1.245; 95% CI, 1.063–1.459; P = 0.007) in patients with PC [ 67 ]. Call et al showed that intraoperative opioid use was not associated with decreased survival in PC surgery [ 68 ].…”
Section: The Effects Of Anesthetics On Pc Progression: From Laborator...mentioning
confidence: 99%